A 3000-yr Annually Laminated Stalagmite Record of the Last Glacial Maximum from Hulu Cave, China. Issue 2 (March 2015) - Duan, Fucai; Wu, Jiangying; Wang, Yongjin; Edwards, R. Lawrence; Cheng, Hai; Kong, Xinggong; Zhang, Weihong
Abstract : A high-resolution, annual layer-counted and 230 Th-dated multi-proxy record is constructed from a stalagmite in Hulu Cave, China. These proxies, including δ 18 O, annual layer thickness (ALT), gray level (GL) and Sr/Ca, cover a time span of 3000 yr from 21 to 24 ka. The physical proxies (ALT and GL) and the geochemical index (Sr/Ca), all primarily reflecting karst hydrological processes, vary in concert and their coherence is supported by wavelet analyses. Variations in the δ 18 O data agree with fluctuations in the ALT and Sr/Ca records on multi-decadal to centennial scales, suggesting that the Hulu δ 18 O signal is strongly associated with varying local rainfall amounts on short timescales. A monsoon failure event at 22.2 ka correlates with a decrease in tropical rainfall, a reduction in global CH 4 and an ice-rafted event in the North Atlantic. This correlation highlights roles of the Asian monsoon and tropical hydrological cycle in modulating global CH 4, because the high-latitude emission was inhibited during the Last Glacial Maximum (LGM). Spectral analysis of the δ 18 O record displays peaks at periodicities of 139, 59, 53, 43, 30, 23 and 19"15 yr. The absence of typical centennial solar cycles may be related to muted changes in ocean circulation during the LGM.